2007
DOI: 10.1097/01.mcg.0000225615.71599.74
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Characteristics of Rhabdomyolysis in Patients With Liver Cirrhosis

Abstract: In conclusion, rhabdomyolysis is developed without specific causes in patients with LC, and it is serious and often fatal particularly in cases in which acute renal failure and severe hepatic dysfunction exist. Our results indicate that LC is the underlying disease for the development of rhabdomyolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…This potential mechanism was raised on the basis of a case reporting a chronological relationship between treatment with rifaximin and rhabomyolysis in a patient with cirrhosis [26]. However, the possibility of muscle toxicity due to rifaximin seems remote due the following reasons: 1/ no cases of rhabomyolisis were reported in the pivotal trial of rifaximin for prevention of recurrent of HE and its long-term followup [15]; 2/ as of July 2019, only two cases of rhabdomyolisis possibly related to rifaximin have been collected in postmarketing safety databases of AlfaSigma (Bologna, Italy) over more than 10 years; 3/ rhabdomyolisis has been reported in the setting of advanced cirrhosis and is idiopathic in 25 to 58% of cases [27]; therefore, cause-effect relationship is difficult to establish; and 4/ no muscle toxicity was found in animal studies in rats and dogs treated with doses of rifaximin equivalent to those used in humans [28].…”
Section: Discussionmentioning
confidence: 99%
“…This potential mechanism was raised on the basis of a case reporting a chronological relationship between treatment with rifaximin and rhabomyolysis in a patient with cirrhosis [26]. However, the possibility of muscle toxicity due to rifaximin seems remote due the following reasons: 1/ no cases of rhabomyolisis were reported in the pivotal trial of rifaximin for prevention of recurrent of HE and its long-term followup [15]; 2/ as of July 2019, only two cases of rhabdomyolisis possibly related to rifaximin have been collected in postmarketing safety databases of AlfaSigma (Bologna, Italy) over more than 10 years; 3/ rhabdomyolisis has been reported in the setting of advanced cirrhosis and is idiopathic in 25 to 58% of cases [27]; therefore, cause-effect relationship is difficult to establish; and 4/ no muscle toxicity was found in animal studies in rats and dogs treated with doses of rifaximin equivalent to those used in humans [28].…”
Section: Discussionmentioning
confidence: 99%
“…It may be related to altered metabolism due to hepatic dysfunction [34]. Even though not a disease "per se", acute myopathy can develop in liver cirrhosis [31]. A subclinical myopathy cannot be excluded in our patient (muscle biopsies were not performed), but no specific muscular symptoms or laboratory signs suggestive for rhabdomyolysis were recorded at any time before transplantation.…”
Section: Idiopathic Rhabdomyolysismentioning
confidence: 96%
“…The mortality rate in this group is high, 31% vs. 10-12% in the general population [31]. Another feature is the recurrence of these episodes as well as the lack of any obvious causes [32].…”
Section: Idiopathic Rhabdomyolysismentioning
confidence: 99%
“…3,4,[7][8][9] In diabetic patients, the well-known vascular changes-such as microangiopathy, atheroma embolization, or vascular occlusion with consequent muscle edema, which reduces capillary blood flow-may contribute to muscle injury. 9 One case series reported that idiopathic rhabdomyolysis often occurs in patients with liver cirrhosis and suggested that defective muscle metabolism due to hepatic dysfunction results in rhabdomyolysis in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…9 One case series reported that idiopathic rhabdomyolysis often occurs in patients with liver cirrhosis and suggested that defective muscle metabolism due to hepatic dysfunction results in rhabdomyolysis in these patients. 8 Acute and chronic alcohol intoxication also has direct toxicity to muscle. 3,7 It was reported that multiple causes were present in 60% of patients assayed and multiple muscle insults are usually needed to produce rhabdomyolysis unless an underlying myopathy is present.…”
Section: Discussionmentioning
confidence: 99%